Single nucleotide substitutions in the matrix metalloproteinase 9 gene in hypertensive individuals of European and South Asian ethnicity in the Far Eastern Federal District - N. G. Plekhova; T. A. Brodskaya; V. A. Nevzorova; N. I. Repina; V. S. Eliseeva (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To determine the association of single nucleotide polymorphism (SNP) -1562C>T (rs3918242) in the matrix metalloproteinase 9 (MMP-9) gene in hypertensive (HTN) in individuals of European and South Asian ethnicity of Primorsky Krai and Sakhalin Oblast.Material and methods. The analysis of conventional and additional risk factors for cardiovascular diseases (35 parameters) in 377 people as a part of regional stage of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study (2014-2019), of whom 240 people of European (Slavic) and 137 people of South Asian (Korean, second- and third-generation immigrants) ethnicity. Substitutions in the MMP-9 gene -1562C>T (rs3918242) was identified by real-time polymerase chain reaction using TaqMan technology.Results. Compared to Koreans, the Slavs have a higher blood pressure (p=0,002). There were no significant differences between ethnic groups (p=0,07) in cardiovascular risk levels using the Systematic Coronary Risk Evaluation (SCORE). Significant differences (p=0,003) were determined in cardiovascular risk levels for healthy Koreans and HTN patients. It was shown that among patients with HTN, the pulse wave velocity exceeded the recommended values in 22,2% of Europeans and in 46,6% of Koreans (p=0,003). The number of hypertensive Europeans and minor MMP-9 rs3918242 T allele exceeded 2,6 times the number of healthy persons (odds ratio, 4,7; 95% confidence interval: 1,1 -7,8 (p=0,03)). MMP-9 rs3918242 T allele in Koreans of the Sakhalin Oblast was not associated with HTN (odds ratio, 0,81; 95% confidence interval: 0,12-5,54 (p=0,83)). Moreover, in South Asian population, heterozygous carriers of T allele prevailed, which significantly (p=0,002) differed from Europeans, who, in general, had a homozygous CC genotype.Conclusion. In Far Eastern Federal District, SNPs in the MMP-9 C-1562T gene were found mainly in hypertensive patients of European ethnicity, while in Koreans, a significant relationship between the carriage of minor T allele in this gene and the presence of HTN was not established.